1992
DOI: 10.1111/j.1540-8159.1992.tb03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Heart Rate Variability in Patients Awaiting Cardiac Transplantation

Abstract: Time and frequency domain parameters of heart rate variability (HRV) were determined in patients with severe endstage heart failure awaiting cardiac transplantation (HTX). These parameters were then correlated with mortality to investigate the performance of HRV in discriminating between groups with high and low risk of death. The standard deviation of five consecutive RR intervals (SDANN) was found to be the parameter with the greatest sensitivity (90%) and specificity (91%). Patients with SDANN values of < 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 10 publications
1
33
1
3
Order By: Relevance
“…Despite the small number of patients in the series, the largest consisting of 102 patients 153 , the results have been consistent. Binder et al 152 , studying patients awaiting heart transplantation, observed that those with SDANN (an index of HRV in the time domain) of 55 ms had a 20-time increase in the risk of death. The authors suggest that HRV is superior to other prognostic factors, such as EF, pulmonary capillary pressure, cardiac index, and serum sodium.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the small number of patients in the series, the largest consisting of 102 patients 153 , the results have been consistent. Binder et al 152 , studying patients awaiting heart transplantation, observed that those with SDANN (an index of HRV in the time domain) of 55 ms had a 20-time increase in the risk of death. The authors suggest that HRV is superior to other prognostic factors, such as EF, pulmonary capillary pressure, cardiac index, and serum sodium.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…In the last five years, HRV has been shown to of important prognostic value in CHF 149,[152][153][154] . Despite the small number of patients in the series, the largest consisting of 102 patients 153 , the results have been consistent.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…Ultra low frequency (ULF) and very low frequency (VLF) are less understood, but are influenced by thermoregulation, physical activity, and the renin‐angiotensin system 18, 23, 24. Decreased HRV has been associated with an increased risk of death in dogs with experimentally induced myocardial infarction and in people with various cardiac diseases 25, 26, 27, 28, 29. Thus, both syncope and decreased HRV are associated with increased risk of death and therefore a history of syncope may be associated with decreased HRV in dogs with MMVD.…”
mentioning
confidence: 99%
“…Similarly, cardiac autonomic tone as measured by short-term heart rate variability (HRV) is a powerful predictor of sudden cardiac death and total mortality in patients with chronic HF. 8,9 HRV can be measured from CIEDs with atrial leads by determining the standard deviation of 5-minute median atrial-atrial intervals (SDAAM) or consecutive ventricular (N-N) intervals (SDANN) over a 24-hour period. Periods of atrial pacing or high atrial rate episodes, including atrial fibrillation, are excluded from HRV analysis.…”
Section: Electrophysiologic Sensorsmentioning
confidence: 99%